Effect of Combined Antibiotics and Biofilm Formation in Some Bacterial Pathogens from Otitis Media among Children in Baghdad, Iraq (Medico Legal Update, 2021)
Otitis media bacterial infections during childhood may contribute to the development of repeatednasopharyngeal infections and it is complicated of recurrent or chronic middle ear diseases, especially withmultidrug resistant strains.The results of antibiotic synergism for the most prevalent three bacterial species, isolated from otitis mediainfections in children, and had the highest antibiotic resistance was revealed that combinations ceftazidimeamikacin and ceftazidime- ciprofloxacin displayed synergistic activity fractional inhibitory concentration(FIC ? 0.5) against the most of tested isolates; Pseudomonas aeruginosa, Porteus mirabilis, and Klebsiellapneumonia. In the biofilm test all tested isolates were showed biofilm production by tissue culture platemethod (TCP), in the present study, the strong biofilm production was most prevalent in Pseudomonasaeruginosa (100%) followed by S. aureus (71.4%). Biofilm formation increases the activity of antibioticsin children otitis media infections and using antibiotics combinations may be essential for optimummanagement of OM patients.